Neurohormonal activation and its relation to outcomes late after repair of tetralogy of Fallot. Issue 6 (28th October 2014) - Heng, Ee Ling; Bolger, Aidan P; Kempny, Alexander; Davlouros, Periklis A; Davidson, Simon; Swan, Lorna; Uebing, Anselm; Pennell, Dudley J; Gatzoulis, Michael A; Babu-Narayan, Sonya V
Abstract : Background: Brain natriuretic peptide (BNP) levels are elevated in patients with repaired Tetralogy of Fallot (rTOF), the clinical significance of which remains uncertain. Methods and results: Ninety consecutive adults (≥16 years) with rTOF (mean age 32.7±11.3 years, 64% men) were prospectively recruited from a single tertiary centre, together with 15 age-matched and gender-matched controls. Patients with rTOF had elevated BNP (8.9 (5.9–14.6) vs 5.4 (2.2–7.5) pmol/L; p<0.01), and BNP activation was common even in asymptomatic patients. Also, atrial natriuretic peptide (6.9 (4.0–9.9) vs 3.3 (1.0–4.0) pmol/L; p<0.01), endothelin-1 (1.14 (0.94–1.48) vs 0.75 (0.44–0.93) pmol/L; p<0.01) and renin (55.0 (45.5–66.5) vs 18.6 (12.0–22.7) pmol/L; p<0.01) were elevated at baseline compared with controls. Interactions between BNP with endothelin-1, cardiothoracic ratio and right atrial area were evident. Eight deaths occurred over a median follow-up of 10 years. On Cox regression analysis, BNP emerged as a strong predictor of death (HR 1.16 per 10 pmol/L, 95% CI 1.05 to 1.29; p<0.01). Survival receiver operating curve analysis revealed an optimum cut-off of BNP ≥15 pmol/L (=52 pg/mL), above which BNP was related to significantly increased mortality (HR 5.40, 95% CI 1.29 to 22.6; p<0.01); absolute mortality at 5 years 19% vs 3% in patients with BNP ≤15 pmol/L. BNP was also a predictor of sustained arrhythmia (HR 2.06 per 10 pmol/L, 95% CI 1.32 to 3.21; p<0.05). Conclusions: Neurohormonal activation is present in adults with rTOF including asymptomatic patients. BNP level ≥15 pmol/L is associated with a fivefold increased risk of death. These data suggest that BNP measurement in patients with rTOF should be incorporated in the periodic risk stratification assessment of these patients under lifelong follow-up.